UTILISATION PATTERN OF ICT (INFORMATION COMMUNICATION TECHNOLOGY) AMONG UNDERGRADUATE VETERINARY STUDENTS IN SOUTHERN STATES OF INDIA - C. Manivannan; K.M. Sakthivel; N. Narmatha; V. Uma; S. Karthikeyan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken with the objective of assessing the utilisation pattern of ICT (Information Communication Technology) among undergraduate veterinary students in southern states of India. Data were collected from 248 final year undergraduate students of 12 veterinary colleges in five southern states of India viz. Tamil Nadu, Kerala, Karnataka Andhra Pradesh and Telangana through pretested questionnaire. The findings of the study revealed that majority of the students studied had 3-4 years of experience in using internet and accessed internet through mobile phone (61.29%). One-third (33.06%) of the students used internet 2-3 days in a week for academic activity while, 30.65% used internet every day for personal activity. The study revealed that students used internet mainly for the preparation of assignments (97.58%). The major problems faced by the students in using ICT tools were slow speed of internet (77.82%) and inadequate number of computers (75.81%) in the institutions. It could be concluded that veterinary students had accessed substantial information technology resources and had knowledge towards computer and internet. Provision of structured information technology training for veterinary students would help them to acquire necessary skills to maximise the utilisation of online veterinary resources.